Om simultantolkning - Aarup, Hanne (HERMES - Journal of Language and Communication in Business, 1989)
The present article deals with simultaneous interpretation from a communicative point of view, placing the act of interpretation within a study of the communicative situation as a whole. It looks into what it takes to perform simultaneous interpretation, in practice, as specified by professional interpreters in a research study and, in theory, through the introduction of linguistic parameters. Models for the process of simultaneous interpretation are set up and discussed, and certain elements of the theory of interpretation are discussed in some detail, such as units, chunks, memory, delay and transformation. Finally, major schools within the theory of interpretation are discussed. Major theses of the Paris school are compared with other theories about interpretation and didactics.